WATER INTEREST INTO SPATIAL PLANNING - Thijs Gerritsen; Bernd Ongena; Slamet Imam Wahyudi; Johan Helmer (International Conference on Coastal and Delta Areas, 2015)
The result of climate change and land subsidence, several cities and communities located in on the north coast of Java faces flooding on a daily basis. The biggest impact of climate change is that bigger peak values in runoff water from higher lands are measured, tidal movements from the Java Sea effects the land more because of sea level rise and the lower surface level. Problems accrue during raining season. Many measurements have already been taken to protect the land from flooding in Indonesia. For example, dikes are built, pumps are installed and retentions areas are appointed. In the Netherlands the â€œwater assessmentâ€ is introduced, which ensures that water management objectives are taken into considerations in relevant spatial planning procedures/ decisions of the central government, province and municipalities. The main focus for this research was to improve the legislation on spatial planning and the procedures at locale scale, which are related in the field of water management. The relevant legislation and procedures are used to derive what the opportunities and limitations are, to implement a kind of water assessment. The final results are two basic concepts which could be used in the context of the Banger Pilot Polder Project in East-Semarang (Jawa Tengah, Indonesia). Nevertheless, the legislation and regulation are mostly similar everywhere in Indonesia. This article and the results can also give an indication of the possibilities for other municipalities and water managers.Keys Words: Water Management, Planning Procedure, Legislation